2013
DOI: 10.1177/0040517513494254
|View full text |Cite
|
Sign up to set email alerts
|

Wearable electronic design: electrothermal properties of conductive knitted fabrics

Abstract: The static and dynamic behavior of a developed electrothermal fabric was studied using an electrothermal model that considers the following fabric parameters: thermal conductivity coefficient, specific heat capacitance, fabric mass, and initial temperature. An experiment was set up to measure the average temperature of the knitted fabric of ordinary materials, namely wool, cotton, and acrylic. These materials were knitted with silver-coated conductive yarns in three loop densities each at an applied electric p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 10 publications
(9 reference statements)
0
26
0
Order By: Relevance
“…(Golmohammadi et al 2017) 3.1.3. Textiles and fibers-Textiles form a broad spectrum of novel materials for flexible biosensing and can be fabricated as fibers (1D), woven, knitted, or fashioned into other non-woven (2D) structures to provide a solid support for the active sensing area (Li et al 2014a;Stoppa and Chiolerio 2014;Windmiller and Wang 2013). These materials, including wool, cotton, or synthetics (nylon, polyester, etc.…”
Section: Paper-papermentioning
confidence: 99%
“…(Golmohammadi et al 2017) 3.1.3. Textiles and fibers-Textiles form a broad spectrum of novel materials for flexible biosensing and can be fabricated as fibers (1D), woven, knitted, or fashioned into other non-woven (2D) structures to provide a solid support for the active sensing area (Li et al 2014a;Stoppa and Chiolerio 2014;Windmiller and Wang 2013). These materials, including wool, cotton, or synthetics (nylon, polyester, etc.…”
Section: Paper-papermentioning
confidence: 99%
“…20 Infrared radio imaging system. An intelligent electric-thermal fabric [21][22][23][24][25][26] (Figure 6(d)) can reach a constant surface temperature under 8 V, 0.87 A after 30 min. It was used as a heat supplier.…”
Section: Evaluation Methodsmentioning
confidence: 99%
“…It was found that the resistance value will decrease dramatically in accordance with an increase in float or tuck elements. Some researchers have investigated the heating properties of conductive fabrics under different voltages [19,20,21]. On the basis of previous research, it has been deduced that the electrothermal properties of EKCF will change in accordance with variations in the knitted structures and applied voltage.…”
Section: Introductionmentioning
confidence: 99%